Assesing carbon mitigation potential for low carbon society development in Lahore Metropolitan area - Ali, Ghaffar; Vilas Nitivattananon; Perera, L.A.S. Ranjith; Shrestha, Rajendra Prasad; Singh, Jagdish; Higher Education Commission(HEC) of Pakistan; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2013)
An important interrogation in climate policy associatedstudyis how much greenhouse gas(GHG)emissionsand energy can be saved, in which sector(s), at what level, anduntilwhen?Normally, two approaches are available to answer thesequestions; the top-downapproach and bottom-up approach.In this study,bottom-up approach is utilized to assesstechnicalcarbon mitigation potential.The bottom-up approach is already in-business toprovide the standard procedure and framework to follow.The previous studies haveconducted carbon mitigation potential assessment using bottom-upapproach,but theydidnot explain how to assesscarbonmitigation potential wherethe dearthof data is a seriousissue,especiallyincities of low-income countrieswhereasusingthealikeframework. Thisgapisfilled by the currentstudyusingthe multidisciplinaryapproach.This studyextendedthe work of pervious investigations and studied slightlyadditionaldimensions.The mainaim of the study wastoassess technical carbon mitigation potential usingthemultidisciplinaryapproach ina metropolitan cityofthe low-incomecountry.The studyarea was Lahore metropolitan area(LMA)of Pakistan.For this purpose, integratedapproach wasakeyand crucialstep, i.e., econometric, energy-environment, and remotesensingmodels/toolswereemployedto conduct the research analyses.Both primary andsecondary data were collected to feed these models/tools for simulation.The bottom-up approach is modified to adjust the missing information, i.e. theuse ofmultiple tools and models help in definingbaseline information before getting into thecarbonreduction target phase.The results illustratethat in the current energy mix of thecity,there is no use of renewable energy such as solar, wind, and biomass, etc.The largestmitigation potential is found in industrial sector (13%)untilthe year2050,while the leastshare is investigated in the commercial sector of the city.The 2050 LCS(low carbonsociety)scenarioproposedthattransport modal shift, energy efficiency in industrialsector,use of renewable energy, and use ofenergy-efficient devicescouldbe major carbonreduction potentialstrategiesofthe cityto be followed.It is concluded thatit is possible toconduct technical carbon mitigation assessmentat local scale or atthe citylevel, wherethedearthof data is a huge problem.By adapting the proposed mitigation policy plan{u2014}theLMA would be able to reduce itsCO2emissions byfifty percentas compared to BaUscenario until 2050.Furthermore,a key contribution of this study was to includeLCLU(Land cover/land use)changeanalysis;this analysis also helpedin validatingthe groundresults ofCO2sources and sinksestimations.Therefore,implementation of mitigationpolicies related to the industrial and transportation sectors would help reducing theCO2emissions of theLMA.Moreover,thismitigation potential studywould serve asrippleeffectin thedata deficientcities of low-income countries.It is also suggested tothe policymakers/planners tolookcarefullyintothe implementation aspectsof these policies at localscaleandnot only at policy and planning level.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Urban Environmental Management
Thesis (Ph.D.) - Asian Institute of Technology, 2013
Keywords: Greenhouse gas mitigation -- Pakistan -- Lahore; Carbon dioxide mitigation -- Pakistan -- Lahore